The roles of black-backed jackals and caracals in issues of human-wildlife conflict in the Eastern Cape, South Africa,The perceived effectiveness of mesopredator control techniques and the mammalian diet of black-backed jackals in the Eastern Cape, South Africa - Murison, Megan Kate (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
[Partial abstract]: Human-wildlife conflict is a widely observed phenomenon and encompasses a range of negative interactions between humans and wildlife. Depredation upon livestock and game species proves to be the prevalent form of this conflict and often results in the killing of carnivores. Within the South African context, despite intense lethal control, two sympatric mesopredators, the blackbacked jackal (Canis mesomelas) and the caracal (Caracal caracal), remain common enough to be considered a major threat to human livelihoods through depredation. Wildlife ranches and livestock farms dominate the landscape in the Eastern Cape Province. Moreover, human-predator conflict within the region is extensive as both the black-backed jackal and caracal are seen to be inimical by landowners. Understanding this conflict is essential for mitigating any potential adverse environmental reactions (i.e. range collapses or extinctions) and requires knowledge of anthropogenic, ecological and environmental factors. I interviewed 73 land owners across five municipal boundaries in the Eastern Cape to quantify perceptions of predator control methods.
Keywords: Black-backed jackal -- South Africa -- Eastern Cape; Human-animal relationships -- South Africa -- Eastern Cape; Predatory animals -- Control -- South Africa -- Eastern Cape; Black-backed jackal -- Food -- South Africa -- Eastern Cape; Black-backed jackal -- Effect of human beings on -- South Africa -- Eastern Cape